2006
DOI: 10.1039/b518312j
|View full text |Cite
|
Sign up to set email alerts
|

Controlled alignment of molecular diodes via ionic assembly of cationic donor–(π-bridge)–acceptor molecules on anionic surfaces

Abstract: Alignment of cationic donor-(pi-bridge)-acceptor molecules via metathesis with a self-assembled monolayer formed from sodium 3-mercapto-1-propanesulfonate results in ultra-thin rectifying Au-S-(CH2)3SO3-/A+-pi-D structures which exhibit optimum current ratios of 450 at +/-1 V for N-methyl-5-(4-dibutylaminobenzylidene)-5,6,7,8-tetrahydroisoquinolinium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…For example, when diode-like molecules are aligned by self-assembly [4][5][6][7][8][9] or Langmuir-Blodgett (LB) deposition 7a,10-13 and contacted by non-oxidizable electrodes, rectification ratios of 2-30 at AE1 V are typical but ratios in excess of 100 have been reported. 14,15 The molecular origin of the electrical asymmetry has been verified from an orientation induced dependence of the bias for rectification 7b,10a and from chemically induced switching of the rectifying behaviour as the donor/acceptor combination is disrupted and then restored. 5-7a,14 There are also many unsubstantiated claims of molecule-induced rectification where the contacts are oxidizable, for example, titanium, [16][17][18] aluminium [19][20][21] or lead: 22 the electrical asymmetry arising from the organic layer is overwhelmed by oxide-induced Schottky barrier effects and assignment of the properties is ambiguous.…”
Section: Introductionmentioning
confidence: 96%
“…For example, when diode-like molecules are aligned by self-assembly [4][5][6][7][8][9] or Langmuir-Blodgett (LB) deposition 7a,10-13 and contacted by non-oxidizable electrodes, rectification ratios of 2-30 at AE1 V are typical but ratios in excess of 100 have been reported. 14,15 The molecular origin of the electrical asymmetry has been verified from an orientation induced dependence of the bias for rectification 7b,10a and from chemically induced switching of the rectifying behaviour as the donor/acceptor combination is disrupted and then restored. 5-7a,14 There are also many unsubstantiated claims of molecule-induced rectification where the contacts are oxidizable, for example, titanium, [16][17][18] aluminium [19][20][21] or lead: 22 the electrical asymmetry arising from the organic layer is overwhelmed by oxide-induced Schottky barrier effects and assignment of the properties is ambiguous.…”
Section: Introductionmentioning
confidence: 96%
“…By definition, a D moiety has a relatively low ionization potential, while the A moiety has a relatively large electron affinity. The experimental verification of AR rectification involved at first Langmuir-Blodgett (LB) or Langmuir-Schaefer (LS) monolayers measured between macroscopic metal electrodes (Al, Mg, Pt [12], and later Au), then chemisorbed monolayers tapped by a macroscopic Au electrode [13], and finally MBJ [4] and scanning tunnelling microscopy [5] for single molecules. Fig.…”
Section: Monolayer Rectifiersmentioning
confidence: 99%
“…As reviewed elsewhere [2,3] eleven rectifiers have been completely characterized in our laboratory, and several others have been reported by others [4,5]. For strictly one-molecule two-probe measurements, mechanical break junctions (MBJ) [6,7], electromigration break junctions (EMBJ) [8], scanning tunnelling microscopy (STM) [9] and scanning probe break junctions (SPBJ) [10] permit the measurement of the electrical current through a single molecule that bridges, say, a 1 nm gap between electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The key challenge is the fabrication of reliable device structures and with sufficiently high yields. Although moderately rectifying junctions have been demonstrated using Langmuir-Blodgett ͑LB͒ films, 5,6,[8][9][10]12 tunnel tips, 11,13,14 and mercurydrop contacts, 6,15,16 they have been plagued by sizeable hystereses and current-voltage instabilities. Recently, it was demonstrated that poly ͑3,4-ethylenedioxythiophene͒:poly͑styrenesulfonic acid ͑PEDT:PSSH͒ films can be used as the top electrode for reproducible large-area tunnel junctions with alkyl dithiols.…”
mentioning
confidence: 99%